Inhibition of LRRK2-Rab10 Pathway Improves Secondary Brain Injury After Surgical Brain Injury in Rats - Li, Jie; Wu, Muyao; Gong, Yating; Tang, Jiafeng; Shen, Jinchao; Xu, Li; Dang, Baoqi; Chen, Gang (Frontiers in Surgery, 2022)
Leucine-rich repeat kinase 2 (LRRK2) is considered as a potential target for the treatment of Parkinson's disease. This protein is expressed in the brain and has been associated with various diseases and lysosomal maintenance. Rab10 is a member of the Rab protein GTPase family that has been recently shown to be a kinase substrate of LRRK2. In addition, LRRK2 and its kinase substrate Rab10 constitute a key stress response pathway during lysosomal overload stress. This study aimed to investigate the potential role and mechanism underlying LRRK2 and its kinase substrate Rab10 involving surgical brain injury (SBI). One hundred and forty-four male Sprague-Dawley rats were examined using an SBI model, and some had received the LRRK2-specific inhibitor PF-06447475. Thereafter, western blotting, immunofluorescence, brain water content analysis, neuronal apoptosis assay, and neurological score analysis were conducted. The results showed that after SBI, LRRK2 and phosphorylated Rab10 (p-Rab10) expression in neuronal cells were upregulated, and administration of PF-06447475 significantly reduced neuronal apoptosis, neuroinflammation, and brain water content 12 h after SBI and improved neurological deficit 72 h after SBI, which is related to the decreased expression of LRRK2 and p-Rab10, and the lessening of lysosomal overload stress. Our research suggests that the inhibition of LRRK2 can effectively interfere with the role of p-Rab10 in promoting the secretion of lysosomal hydrolase in lysosomal overload stress after SBI, thereby reducing neuronal apoptosis and inflammation after SBI and playing a major role in brain protection.